2018
DOI: 10.14744/phd.2018.87699
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Schizophrenia Patients Attending the Rehabilitation Programmes Conducted in Community Mental Health Center In Terms of some Demographic Variables, Characteristics related to the Ailment, Adaptation to the Treatment and Self-Efficacies

Abstract: Bu çalışmanın amacı, bir Toplum Ruh Sağlığı Merkezi (TRSM)'nde uygulanan rehabilitasyon programlarına katılan ve katılmayan şizofreni hastalarının bazı sosyodemografik ve hastalıkla ilişkili özellikleri ile tedaviye uyumları ve öz yeterliliklerini tanımlamaktır.Gereç ve Yöntem: Karşılaştırmalı-tanımlayıcı nitelikte planlanan bu çalışma Ocak-Mart 2016 tarihleri arasında Amasya'da bulunan Toplum Ruh Sağlığı Merkezi'nde yapıldı. Araştırmanın örneklemini, şizofreni tanısı ile takip edilen, rehabilitasyon programla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
4
0
3
Order By: Relevance
“…Bu sonuçlar yapılan birçok çalışma ile benzerlik göstermektedir. [27][28][29][30] Şizofreni hastalarında hastalık başlangıç yaşı ortalamalarının 16-21 yaş aralığında olduğu bildirilmiştir. [30,31] Hastalık başlangıç yaşı açısından bizim araştırmamızın sonuçlarının yapılan çalışmaların sonuçlarıyla benzer olduğu görülmüştür.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Bu sonuçlar yapılan birçok çalışma ile benzerlik göstermektedir. [27][28][29][30] Şizofreni hastalarında hastalık başlangıç yaşı ortalamalarının 16-21 yaş aralığında olduğu bildirilmiştir. [30,31] Hastalık başlangıç yaşı açısından bizim araştırmamızın sonuçlarının yapılan çalışmaların sonuçlarıyla benzer olduğu görülmüştür.…”
Section: Discussionunclassified
“…[27][28][29][30] Şizofreni hastalarında hastalık başlangıç yaşı ortalamalarının 16-21 yaş aralığında olduğu bildirilmiştir. [30,31] Hastalık başlangıç yaşı açısından bizim araştırmamızın sonuçlarının yapılan çalışmaların sonuçlarıyla benzer olduğu görülmüştür. Hastaların eğitim durumu incelendiğinde, yapılan diğer çalışmalardan [27][28][29][30][31] farklı olarak %45 oranında hastanın lise mezunu olduğu bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Moreover, evaluating the effect also extends from superficial symptoms, cognition ability and skills to deeper levels, such as psychological feelings and quality of life. Results from previous meta-analyses and pilot studies have demonstrated the effects of these rehabilitation efforts, including improvement of patients' symptoms [ 10 , 18 20 ], increase in medication compliance [ 21 , 22 ], improvement of life skills [ 23 ], improvement of mood [ 22 ], increases in self-esteem [ 24 , 25 ], and improvement in quality of life [ 10 , 11 , 18 , 24 ] among others. However, most of these studies represent researchers’ perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evaluating the effect also extends from super cial symptoms, cognition ability and skills to deeper levels, such as psychological feelings and quality of life. Results from previous meta-analyses and pilot studies have demonstrated the effects of these rehabilitation efforts, including improvement of patients' symptoms [10,[18][19][20], increase in medication compliance [21,22], improvement of life skills [23], improvement of mood [22], increases in self-esteem [24,25],and improvement in quality of life [10,11,18,24] among others. However, most of these studies represent researchers' perspectives.…”
Section: Introductionmentioning
confidence: 99%